Coexistence of Late-Onset Systemic Lupus Erythematosus With Focal Segmental Glomerulosclerosis and Lichen Planus: A Case Report - Betül SARGIN,; Gülcan GÜRER, (Archives of Rheumatology, 2017)
Lichen planus and lupus nephritis with late-onset systemic lupus erythematosus (LO-SLE) may occur concomitantly. However, coexistence of LO-SLE with focal segmental glomerulosclerosis and lichen planus has not been defined. In this article, we report a 57-year-old male patient presenting with lichen planus and focal segmental glomerulosclerosis who was subsequently diagnosed with LO-SLE. To the best of our knowledge, this is the first case of LO-SLE presenting with lichen planus and focal segmental glomerulosclerosis.